J. VAITKEVIČIUS’ INVITATION TO PRACTICE TEACHER SELF-AWARENESS IN EDUCATION - Tijūnėlienė, Ona; Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 2009)
Every generation of teachers moves along the way to changes in education performing two main functions: teaching and education of young children. Teaching and educating is a highly personal activity and experience. The human aspect – a teacher as the subject of the professional activity – becomes a major factor in teaching practice. Nowadays, the problems of the subject as a phenomenon of social reality is becoming increasingly more topical (Saiko, 2006). The teacher personality factor have been recognized in the profession; however, works providing more exhaustive analysis of the teacher self-awareness are not numerous. This article reviews teacher’s self-awareness as presented in J.Vaitkevičius’ works in terms of pupil education and development. The first part of the article stresses the relationship between teacher self-awareness and personal / social progress of young people. It says that the way to this progress has to begin with the teacher and his / her self-awareness. The article develops the idea that teacher’s self-awareness is among the most important influencing factors on the life and development of many young people. The benefit of teacher’s self-awareness in teaching and educating is supported by the works of some scholars. The second part of the article deals with reflection – as an instrument of teacher’s self-awareness offering possibilities to discover one’s external and internal personal differences which can acquire distinctive kinds of teacher actions and judgements in profesional practice.